Stimulants for depression: On the up and up?. (March 2016) - Malhi, Gin S; Byrow, Yulisha; Bassett, Darryl; Boyce, Philip; Hopwood, Malcolm; Lyndon, William; Mulder, Roger; Porter, Richard; Singh, Ajeet; Murray, Greg
The use of traditional psychostimulants (methylphenidate and dexamphetamine) and stimulant-like drugs (modafinil and armodafinil) for the treatment of depression is a growing concern given the lack of research evidence supporting their effectiveness. The current article describes the role of stimulants in treating depression – specifically their risks and benefits and their potential use alongside antidepressants. Clinically, the rapid amelioration of depressive symptoms with traditional psychostimulants is often dramatic but short-lived, and this suggests that they likely operate via different mechanisms to conventional antidepressants. More importantly, there is little evidence from randomised controlled trials supporting their efficacy in treating depression, although modafinil has been shown to be effective in reducing prominent depressive symptoms, such as fatigue. Research is urgently required to clarify psychostimulants' mechanisms of action and to evaluate their long-term benefits and risks in the treatment of major and bipolar depression. Ultimately, specificity of action needs to be determined to inform the sophisticated clinical use of psychostimulants in the management of depression. Until then they should only be prescribed if absolutely necessary, and even then their prescription should be facilitatory and time limited unless it is for investigational purposes.